Commercial success of innovation: the roles of R&D cooperation and firm age - Heli Koski (The Research Institute of the Finnish Economy (ETLA), 2015)
Data comprising 1790 Finnish firms and covering the years 2006-2012 suggest that turnover from innovative sales per employee were higher for both young firms - particularly for young innovative companies (or YICs) - and older incumbents that had broad innovation collaboration involving vertical, horizontal and institutional partners. Younger firms with simultaneous horizontal and vertical innovation collaboration tend to also generate higher turnover due new products and services, while this type of collaboration did not appear statistically significant in innovation production function for older incumbents. Our data further indicate that not only the relationship between inventor age and patentable inventions at the inventor level is inversely u-shaped – as previous studies report - but also the relationship between employee age structure and the generation of commercially successful products and services at the firm level follows the same pattern. High education of employees distinguished particularly the top performers from others at the highest 0.9 quantile of turnover from innovative sales per employee. Furthermore, firms with relatively highly educated employees and broad innovation collaboration had clearly higher returns from innovative sales per employee than other firms, while none of the innovation collaboration types was statistically significantly related to the innovation output of firms with relatively low education of employees.
Keywords: L2; O31; O32; 330; innovation performance; R&D cooperation; human capital